Quantum message authentication scheme based on remote state preparation. (5th October 2018) - Kang, Min-Sung; Choi, Yeon-Ho; Kim, Yong-Su; Cho, Young-Wook; Lee, Sang-Yun; Han, Sang-Wook; Moon, Sung
Abstract: We propose a quantum message authentication scheme that provides integrity and origin authentication using a remote state preparation. Authentication is one of the security services that must be provided in secure communication. Quantum message authentication is the base scheme for realizing quantum authentication that is known to be a secure technique even in a forthcoming quantum computer environment. The proposed scheme creates a quantum message authentication code (QMAC) with only a single qubit measurement. It is therefore easy to implement and operate compared to existing technology that normally generates a QMAC with a Bell measurement or controlled unitary operation. For security analysis, we design a quantum random oracle model based on the random oracle model and demonstrate the quantum collision resistance with it. From the analysis, the probability of the quantum collision is 0.69 N per qubit, where N is the size of the message sequence. Since the probability of quantum collision in the case of N  ≥ 13 becomes extremely low of under 0.8%, we confirm that the proposed scheme guarantees the integrity and origin authentication of the message.